Prevalence of mental health problems and associated factors of Thai healthcare workers during the first wave of COVID-19 pandemic: 10.55131/jphd/2022/200109 - Komwong, Daoroong; Prasanthanakul, Jirakeat; Phanasathit, Muthita; Wongwan, Taniya (Journal of Public Health and Development, 2022)
The purpose of this cross-sectional, national online survey was to assess the magnitude of mental health problems and to identify job task and organizational factors associated with mental health outcomes during the COVID-19 pandemic among healthcare workers in Thailand. The data were collected during the first wave of the COVID-19 pandemic (May 1-15, 2020). Study participants were 417 healthcare workers in public health care facilities of all 12 health regions in Thailand. Demographic data, job task and organizational factors, and mental health outcomes were collected. The mental health outcome was assessed by the Thai version of the Depression, Anxiety, and Stress Scale - 21 Items (DASS-21). Multivariate logistic regression was performed to identify factors associated with mental health outcomes. The results found that most participants were women (77.7%). The largest proportion of participants were nurses (40.5%), followed by public health officers (20.9%). The average age of participants was 41.82 years (SD=10.06). We identified 21.1%, 22.5%, and 15.3% of all respondents had mild to extremely severe depression, anxiety and stress, respectively. Caring for inpatients with COVID-19 was associated with anxiety (aOR=3.41; 95% CI= 1.34, 8.68) and stress (aOR =2.96; 95% CI= 1.11, 7.95). Lack of readiness among management to reduce infection risk, inadequate PPE, working with the fear of being infected and transmitting infection when returning home, and having patients who did not strictly adhere to guidelines were identified as risk factors for all mental health outcomes, after adjustment for confounding. Organizational approaches, such as effective management can help reduce infection of both patients and healthcare providers. These strategies may also protect the mental health of health care workers in a “new, emerging phase” or a future wave of COVID-19 cases.